Structural optimization of an engine crankshaft-bearing system based on deformation coordination analysis - You, Xiaomei (Strojniški vestnik, 2026)
This study investigates the deformation coordination of an engine crankshaft-bearing system and presents a tolerance-based method to improve stiffness matching. First, a continuous-beam analytical model is developed to derive bearing support reactions, with its accuracy being validated through a three-dimensional finite element model under worst-case loading conditions. Then the Reynolds equation is combined with the Gumbel boundary condition to explain hydrodynamic effects. Based on the journal eccentricity, the load-carrying coefficient is described by fitting an exponential function. Finally, using the relative bearing clearance as the design variable, a clearance-optimization model is formulated to minimize the variance in support displacements. The results show that the sequential quadratic programming method after particle swarm optimization can improve the deformation coordination by 31 %. This method can provide a practical and computationally efficient guideline for improving structural stiffness matching and lubrication performance in crankshaft-bearing system design.
Keywords: clearance optimization; crankshaft-bearing system; deformation coordination; hidrodinamično mazanje; hydrodynamic lubrication; optimizacija zračnosti; sistem ročične gredi in ležajev; stiffness matching; structure optimization; strukturna optimizacija; ujemanje togosti; usklajenost deformacij